2019
DOI: 10.1007/s00018-019-03291-2
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of Foxg1 in supporting cells increases the trans-differentiation of supporting cells into hair cells in the neonatal mouse cochlea

Abstract: Foxg1 is one of the forkhead box genes that are involved in morphogenesis, cell fate determination, and proliferation, and Foxg1 was previously reported to be required for morphogenesis of the mammalian inner ear. However, Foxg1 knock-out mice die at birth, and thus the role of Foxg1 in regulating hair cell (HC) regeneration after birth remains unclear. Here we used Sox2 CreER/+ Foxg1 loxp/loxp mice and Lgr5-EGFP CreER/+ Foxg1 loxp/loxp mice to conditionally knock down Foxg1 specifically in Sox2+ SCs and Lgr5+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
99
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(99 citation statements)
references
References 96 publications
0
99
0
Order By: Relevance
“…In the auditory system, HCs and SGNs are very important for hearing ability; HCs convert the sound waves into electrical signals, and SGN transmit the electrical signals into the auditory cortex for hearing ability [29]. In a mammal's cochlea, HCs and SGNs are vulnerable for multiple damages, including noise, gene mutation, ototoxic drugs, inflammation, and aging [30][31][32][33][34]; while the mammal's cochlea only have very limited HC and SGN regeneration ability, majority of the damaged HC and SGN cannot be spontaneously regenerated [35][36][37][38][39][40][41]. Thus, hearing loss is usually irreversible, and AN may come from the damage of IHC and SGNs.…”
Section: Discussionmentioning
confidence: 99%
“…In the auditory system, HCs and SGNs are very important for hearing ability; HCs convert the sound waves into electrical signals, and SGN transmit the electrical signals into the auditory cortex for hearing ability [29]. In a mammal's cochlea, HCs and SGNs are vulnerable for multiple damages, including noise, gene mutation, ototoxic drugs, inflammation, and aging [30][31][32][33][34]; while the mammal's cochlea only have very limited HC and SGN regeneration ability, majority of the damaged HC and SGN cannot be spontaneously regenerated [35][36][37][38][39][40][41]. Thus, hearing loss is usually irreversible, and AN may come from the damage of IHC and SGNs.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding plasticity and reconstruction of neural network after hearing injury, Ctpb2 was usually used to label the synapse, and the number of innervated synapses was compared to assess the structure and function of neural connections (Zhang et al, 2019). Our results suggest that blebbistatin has a good protective effect on synaptic damage caused by neomycin in HCs.…”
Section: Discussionmentioning
confidence: 84%
“…The Foxg1 gene is a dose-sensitive gene, it can antagonize the proapoptotic effect of Foxo3 [22] and promotes hepatocellular carcinoma epithelial-mesenchymal transition [23]. As Shasha Zhang's reported, knocking out the Foxg1 gene will increase differentiation of newborn mouse cells [24]. Studies have found that cyclin D plays an important role in cell proliferation, which has three subfamilies: cyclin D1, cyclin D2 and cyclin D3.…”
Section: Introductionmentioning
confidence: 99%